Menopausal symptoms: prediction of quality of marital relationship among couples - Noshi Iram Zaman; Sundas Shakoor; Shazia Yusuf (Journal of Mind and Medical Sciences)
Objective. The current study determined the association between menopausal symptoms and marital quality of life, and explored the role of several demographic variables (education, occupation, and income) on these symptoms. Materials and Methods. The purposive sample included 180 married couples. Wives experiencing premenopause, perimenopause, and postmenopause 35 to 60 years old (M=45.21 & SD=7.47) were recruited from Islamabad and Rawalpindi, Pakistan. Two assessment instruments were used: Menopause Rating Scale- MRS for menopausal symptoms, and ENRICH Marital Satisfaction Scale- EMS for quality of marital relationship. Results. Wives’ quality of marital relationship was not significantly predicted by menopausal symptoms whereas husbands’ quality of marital relationship was significantly predicted by psychological (but not physical) symptoms of menopause. Also, several differences in menopausal symptoms and quality of marital relationship were found in relation to demographic variables. Conclusions. Clinicians should consider the relevance of psychological symptoms of menopause, and not just physical symptoms, in relationship assessment, a result that has research, practice, education and public health implications. Furthermore, possible cultural differences in the perception of menopausal effects should be addressed in greater depth.